Experimental evaluation of the anti-ulcer activity of the ethanolic extract of grape (Vitis vinifera) seed in wistar albino rats against aspirin plus pylorus ligation induced gastric ulcer model - Ingale, Anand M.; Pinnelli, Venkata Bharat Kumar; Rajendran, Vijaya (International Journal of Basic & Clinical Pharmacology, 2016)
Background: There is an increased demand for newer safer drugs for the treatment of peptic ulcer disease as its incidence is increasing gradually in view of changing lifestyle and stress. The objective of this study was to evaluate the anti-ulcer activity of ethanol extract of seeds of Vitis vinifera. Methods: The ethanol extract of Vitis vinifera was investigated for its anti-ulcer activity in rats against Aspirin plus Pylorus ligation induced gastric ulcer. The antiulcer activity was assessed by determining and comparing gastric volume, pH, free and total acidity; ulcer number and its inhibition, ulcer severity and ulcer index. Results: A significant antiulcer activity was observed. Pylorus ligation model showed significant (p<0.01) reduction in gastric volume, free acidity and ulcer index as compared to control. Conclusions: This present study indicates that Vitis vinifera seed extract have potential anti-ulcer activity in the model tested.